Diseño, automatización e implementación de la línea de producción para productos tipo snacks - Rojas-Solano, Manuel (Instituto Tecnológico de Costa Rica, 2012)
The advance of technology has increasingly influenced many different fields, in which food industry was no exception. That is the reason everyday people look for more efficient processes to get benefits during the production process. DEMASA Company has seen this technological raise as a chance to get first class products to be marketed in national and international marketplaces. What DEMASA expects by developing this project is to improve the production process of the lines that complement TOSTY Brand, especially potato chips such as: “PAPITOSTY” and “PAPIOLAS.” This because currently there are not controls over the variables that influence products fabrication regarding the potato hopper, quantity of raw material in the process, water, air, fryer temperature, conveyor belt speed, and engine control. If these variables are not rightly manipulated, there can appear several problems which can be: stop on the production waste of air and water, turn engines on unnecessarily, inappropriate fry temperature, or something even more serious such as the drop down of the products final quality or problems with product’s quantity which may produces economical loss to the company. By analyzing the situation, it can be concluded that those problems can be avoided and they are a consequence of the lack of control variables during the process. The solution to the problems is to perform a centralized system where people can have control and monitor the production process variables.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2012.
Keywords: Control automático; Ethernet; PLC; Pantalla táctil; Válvula solenoide; Variador de frecuencia; Motores; Lógica en escalera